Dynamics of maximal strength and strength endurance indicators in rhythmic gymnasts - Guseva, E. V.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to profile the maximal strength and strength endurance variations with age in the 6-10 year old female rhythmic gymnasts.